THE ASSOCIATION OF FOOD FLAVOR AND APPEARANCE WITH FOOD WASTE IN HOSPITALIZED PATIENTS AT NGIMBANG LAMONGAN HOSPITAL - A’yun, Salsabila Qurrotu; Rohmawati, Ninna; Astuti, Nur Fitri Widya (Universitas Airlangga, 2025)
Food waste at Ngimbang Lamongan Regional Hospital during the first semester of 2022 exceeded 20%, with the highest food waste was in May at 29.12%. Meanwhile, the results of a preliminary study in 2024 showed food waste in May was 23.04%, June 24.34%, and July 24.46%. The purpose of this study was to analyze the relationship between flavor and appearance of food and food waste among inpatients at Ngimbang Lamongan Hospital. This study used a cross-sectional approach and was conducted at Ngimbang Lamongan Hospital in August 2024 and October 2024. A total of 96 respondents were selected through purposive sampling. Data on food flavor and appearance collected through interview, while food waste measured using a visual Comstock form. Over a 10-day menu cycle, food waste average was 29.48%, with 60.42% of respondents reporting food waste exceeding 20%. The highest food waste occurred during lunch (32.36%), while staple foods being the most waste category (37.90%). The results of Chi-square test indicated that the most components of food flavor and appearance had a significant relationship with food waste (p-value <0.05). Specifically, food flavor attributes (aroma, seasoning, cooking level of the food, temperature, and texture of food) and appearance factors (color, shape, and presentation of food) were significantly associated with food waste, while portion size showed no significant relationship.